Encapsulation of Coriandrum sativum Essential Oil in Nanoemulsion and Study Their Antioxidant and Biological Activities Against Food Associated Pathogenic Bacteria - Randa Mohammed Dhahi; Aseel Mahmood Ibrahim Al-Mashahedah (Journal of Nanotechnology)
Foodborne diseases are still a serious global health issue, especially in developing countries, this study aimed to encapsulate the essential oils of coriander (Coriandrum sativum L.) in nanoemulsion and explore its efficiency as an antioxidant and antibacterial agent against foodborne pathogens. The Coriandrum sativum oil nanoemulsion (CNE) was fabricated using Tween 80 as an emulsifier. Ultrasonication was applied for 8 min to yield a homogenous nanoemulsion. The chemical profile of essential oils was investigated by gas chromatography/mass spectrometry (GC-MS). The physicochemical properties of CNE were examined by dynamic light scattering (DLS), UV-visible (UV-Vis) spectrophotometer, scanning electronic microscopic (SEM), and atomic force microscope (AFM). The CNE was assessed against Escherichia coli and Klebsiella pneumoniae implicated in foodborne. The GC-MS analysis showed that linalool was the main component in coriander essential oil with 64.06%. The biofabricted CNE had a Z-average of 147.5 nm and a zeta potential of 1.9 mV. SEM images showed that the CNE was spherical. AFM images revealed that the CNE had a moderately flat surface. Interestingly, CNE exhibited high efficiency as an antioxidant and antibacterial agent; this in turn gives it the potential to be a candidate as a natural active bio-based preservative used to tackle food poisoning besides adding value to food.